Perbandingan Hasil Belajar Praktikum Histologi Secara Tatap Muka dan Daring Pada Mahasiwa Fakultas Kedokteran Universitas Riau Tahun 2019 – 2020 - Winarto winarto; Annisaa Soraya (Fakultas Kedokteran Universitas Riau, 2023)
The impact of the COVID-19 pandemic has caused many countries to implement online education. The Faculty of Medicine, Universitas Riau carried out online histology learning with demonstration videos and slide shows using the ZOOM platform during the pandemic. The study aims to compare the results of the Histology practicum exam between face-to-face and online learning methods for students of the Faculty of Medicine, University of Riau in 2019 and 2020. This research is an analytical research with a cross-sectional approach. The average results of histology practicum scores in three blocks, namely the Nervous and Locomotor System block, the Circulatory and Respiratory System block, and the Digestive, Metabolic and Endocrine System blocks in 2019 using face-to-face methods and in 2020 using online methods with a p-value of 0.000. The conclusion of this study is that learning histology practicum online methods is better than face-to-face methods.